2009
DOI: 10.1161/circinterventions.108.799361
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Therapeutic Neovascularization Using Peripheral Blood Mononuclear Cells for Limb Ischemia

Abstract: Background-Injection of bone marrow mononuclear cells has been reported to promote neovascularization of ischemic tissues effectively. We found that peripheral blood mononuclear cells were as efficient as bone marrow mononuclear cells for the treatment of limb ischemia in animals and showed that this treatment was feasible and safe in no-option patients with limb ischemia. However, the long-term outcome of such therapy has not been investigated. Methods and Results-We retrospectively analyzed the data for 42 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 33 publications
4
54
0
1
Order By: Relevance
“…[1][2][3][5][6][7][8][9]22,23 Unfortunately, there have been only a few studies on long-term follow-up of clinical symptoms and outcomes, including major amputation, for more than 2 years after cell therapy. 4,15,24,25 These studies also clearly showed that cell therapy reduces the rate of major amputation, one of the primary end points. In addition, there has been no information on predictors of major amputation with BM-MNC implantation.…”
Section: Discussionmentioning
confidence: 89%
“…[1][2][3][5][6][7][8][9]22,23 Unfortunately, there have been only a few studies on long-term follow-up of clinical symptoms and outcomes, including major amputation, for more than 2 years after cell therapy. 4,15,24,25 These studies also clearly showed that cell therapy reduces the rate of major amputation, one of the primary end points. In addition, there has been no information on predictors of major amputation with BM-MNC implantation.…”
Section: Discussionmentioning
confidence: 89%
“…Many studies using different methods, such as vascular endothelial growth factor (VEGF)‐related gene transfer 6, 7, bone‐marrow mononuclear cell (BMMNC) 8, 9, 10, 11, 12, PBMNC 13, 14, 15, 16, 17, 18, or CD34+ cell 2, 3, 4 transplantation, have been completed and have proven their safety and efficacy. The long‐term outcome after CD34+ cell therapy in CLI patients was already reported by Kinoshita et al in 2012 19.…”
Section: Discussionmentioning
confidence: 99%
“…Critical limb ischemia (CLI) is the most advanced stage of PAD. It often coincides with ischemic ulceration and/or gangrene [1], and significantly decreases a patient’s quality of life. It is difficult to manage using current treatment modalities.…”
Section: Introductionmentioning
confidence: 99%